2015
DOI: 10.1194/jlr.m054544
|View full text |Cite
|
Sign up to set email alerts
|

Relative roles of ABCG5/ABCG8 in liver and intestine

Abstract: ABCG5 (G5) and ABCG8 (G8) form a sterol transporter that acts in liver and intestine to prevent accumulation of dietary sterols. Mutations in either G5 or G8 cause sitosterolemia, a recessive disorder characterized by sterol accumulation and premature coronary atherosclerosis. Hepatic G5G8 mediates cholesterol excretion into bile, but the function and relative importance of intestinal G5G8 has not been defined. To determine the role of intestinal G5G8, we developed liver-specific (L-G5G8−/−), intestine-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 47 publications
6
96
0
Order By: Relevance
“…Studies concerning Pctp −/− mice have found that body fat composition was increased in Pctp −/− mice [49,51]. The function of Abcg5 is to maintain sterol balance in vertebrates [52]. More studies are required to clarify the compounds in PTE that may activate Lpin-1, Pctp, and Abcg5 gene expression through directly interaction with PPARα.…”
Section: Discussionmentioning
confidence: 99%
“…Studies concerning Pctp −/− mice have found that body fat composition was increased in Pctp −/− mice [49,51]. The function of Abcg5 is to maintain sterol balance in vertebrates [52]. More studies are required to clarify the compounds in PTE that may activate Lpin-1, Pctp, and Abcg5 gene expression through directly interaction with PPARα.…”
Section: Discussionmentioning
confidence: 99%
“…The proteins encoded by the ABCG5 and ABCG8 genes located in head-to-head orientation on exon 13 of chromosome 2p21 are expressed in both the liver and intestine and function to regulate cholesterol re-excretion (7,8,19e21,26,27). ATP binding cassette proteins G5/G8 prevent accumulation of sterols, decrease sterol absorption in the intestine and increase sterol excretion from the liver into the bile (26,27). Mutations in either ABCG5 or ABCG8 transporters cause hyperabsorption and decreased biliary excretion of sterols, leading to sitosterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were centrifuged for 10 minutes at 1.500 Âg at þ4 C, followed by the removal of serum and plasma and then were stored at e20 C. Fasting glucose, total cholesterol, triglyceride, high-density lipoprotein (HDL) cholesterol, lowdensity lipoprotein (LDL) cholesterol and very low-density lipoprotein (VLDL) cholesterol were determined in the study groups by standard laboratory methods in the Istanbul University and Haseki Training and Research hospitals (26,27). In addition, body mass index (BMI; weight in kilograms divided by the square of the height in meters) values were calculated and categorized according to World Health Organization recommendations.…”
Section: Biochemical and Demographic Analysismentioning
confidence: 99%
“…ABCG5 and ABCG8 are expressed in the liver and small intestine, where they function to excrete sterols into bile and limit intestinal absorption of dietary plant sterols [9] . Genetic variation in ABCG5/8, simultaneously influence plasma and biliary cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%